PENGARUH KOMPENSASI DAN MOTIVASI TERHADAP KEPUASAN KERJA KARYAWAN PT. BUKAKA TEKNIK UTAMA, TBK BOGOR - Freddrick Tiagita P (Jurnal Ekonomi dan Industri, 2019)
A positive condition for the company is believed by the government in 2018 to help build infrastructure in several major cities in Indonesia such as toll roads and the development of ports and airports. On the other hand the achievement of targets given by the company to employees cannot be achieved maximally, where in general employees feel dissatisfaction in their work. The purpose of this study is to analyze the influence both simultaneously and partially compensation and motivation on the performance of employees at PT. Bukaka Teknik Utama, Tbk Bogor. This research is a quantitative research involving 30 employees. The analysis technique uses simple and multiple regression analysis. The results of the study are there are influences both simultaneously and partially compensation and motivation on the performance of employees at PT. Bukaka Teknik Utama, Tbk Bogor.